Um componente em discussão no currículo das licenciaturas em matemática: a prática de ensino - Santos, Francisco de Assis dos (2008)
This research investigates the development of the teaching practice as a curriculum component of the Graduation Courses in Mathematics. It identifies the different existing concepts with regard to this practice. It also places under discussion to what extent the understanding of the teaching practice has been assimilated, mainly by the mathematics teacher trainer, and the contradicting processes through which this practice strengthens and/or hides the interdisciplinarity intrinsic to the teaching object, considered as school/curriculum knowledge. This research is based on the National Curriculum Guidelines for the initial training of mathematics teachers, and also on the State University of Alagoas (UNEAL) Educational Project for the Graduation Course in Mathematics. The subjects involved in the study were: the Course Coordinator, as well as some graduation students and teachers of teaching practice of the mentioned University. The methodology used was the case study with a qualitative approach. Data collection was carried out through interviews with the course coordinator, students and teachers, who, from then on, will be respectively identified by Coordinator, Student 1, Student 2, Student 3, Student 4, Teacher (P). Our aim is to analyze the different conceptions and/or approaches to teaching practices adopted or addressed by the subjects interviewed, and compare them to the ones presented in the Course Educational Project and in the National Curriculum Guidelines for the initial training of mathematics teachers. We also intend to address the teachers understanding of such practice and the students degree of satisfaction